Sparse scalegram decomposition algorithm for condition monitoring of rotary equipment - Y. P. Aslamov; I. G. Davydov; N. V. Kosmach; R. V. Tolkach (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The article describes an algorithm for the sparse decomposition of vibration signals scalogram for searching of the frequency domains with a significant energy contribution. The developed algorithm is proposed to be used for monitoring the technical condition of rotary equipment. The article presents the testing results of the sparse scalegram decomposition algorithm on the vibration signals of industrial equipment.